Suggestive Evidence for Causal Effect of Leptin Levels on Risk for Anorexia Nervosa: Results of a Mendelian Randomization Study - Peters, Triinu; Antel, Jochen; Naaresh, Roaa; Laabs, Björn-Hergen; Föcker, Manuel; Albers, Nicola; Bühlmeier, Judith; Hinney, Anke; Libuda, Lars; Hebebrand, Johannes (Frontiers in Genetics, 2021)
Genetic correlations suggest a coexisting genetic predisposition to both low leptin levels and risk for AN. To investigate the causality and direction of these associations, we performed bidirectional two-sample Mendelian randomization (MR) analyses using data of the most recent genome-wide association study (GWAS) for AN and both a GWAS and an exome-wide-association-study (EWAS) for leptin levels. Most MR methods with genetic instruments from GWAS showed a causal effect of lower leptin levels on higher risk of AN (e.g. IVW b=-0.923, p=1.5x10-4). Because most patients with AN are female, we additionally performed analyses using leptin GWAS data of females only. Again, there was a significant effect of leptin levels on the risk of AN (e.g. IVW b=-0.826, p=1.1 x 10-04). MR with genetic instruments from EWAS showed no overall effect of leptin levels on the risk for AN. For the opposite direction, MR revealed no causal effect of AN on leptin levels. If our results are confirmed in extended GWAS data sets, a low endogenous leptin synthesis represents a risk factor for developing AN.